The effect of a training curriculum to develop motor speed with wheelchairs for handicapped tennis players (Journal of the College of Basic Education, 2022)
To identify the effect of the training curriculum in developing motor speed in wheelchairs for disabled tennis players, and the researcher used the experimental method using the two equal groups (experimental and control) with two pre and post tests due to its suitability to the nature of the research. The Iraqi national tennis team for the disabled (junior category), as they were randomly divided into two groups, experimental and control, each group consisting of (5) players, and after applying the training curriculum prepared by the researcher for a period of (8) weeks, with a number of (24) training units. Three units per week, and the duration of the unit is (30) minutes, in which movement exercises are given using wheelchairs.